RENEWABLE ENERGY SOURCES: AN OVERVIEW OF CLEAN ALTERNATIVES (CIPEEX, 2023)
A STUDY WAS CARRIED OUT ON RENEWABLE ENERGY SOURCES IN A GLOBAL CONTEXT. THE INVESTIGATION BEGAN BY ADDRESSING THE ISSUE OF THE ABUNDANCE OF THESE RESOURCES AROUND THE WORLD, HIGHLIGHTING THEIR INTRINSIC IMPORTANCE IN THE TRANSITION FROM AN ENERGY MATRIX DEPENDENT ON FOSSIL FUELS TO A MORE SUSTAINABLE AND ENVIRONMENTALLY FRIENDLY ONE. IT THEN EXAMINED IN DETAIL THE EVOLUTION AND REMARKABLE ADVANCES THAT THESE ENERGY SOURCES HAVE EXPERIENCED IN RECENT YEARS. TO ILLUSTRATE THIS EVOLUTION, A GRAPH WAS PRESENTED THAT CLEARLY AND OBJECTIVELY DEMONSTRATES THE STEADY GROWTH OF RENEWABLE ENERGIES OVER THE LAST FIVE YEARS, SIGNALING SIGNIFICANT PROGRESS TOWARDS A GREENER AND MORE RESILIENT ENERGY MATRIX.FINALLY, THE CLASSIFICATION OF THE MAIN RENEWABLE ENERGY SOURCES, INCLUDING SOLAR, WIND, GEOTHERMAL, OCEAN, BIOENERGY AND HYDROELECTRIC, WAS EXPLORED, HIGHLIGHTING THE INDIVIDUAL ROLES THEY PLAY IN REDUCING GREENHOUSE GAS EMISSIONS AND DRIVING THE SEARCH FOR CLEANER AND MORE SUSTAINABLE ENERGY SOLUTIONS FOR THE FUTURE. AS A RESULT, THIS WORK OFFERS A COMPREHENSIVE AND UP-TO-DATE OVERVIEW OF THE STATE OF RENEWABLE ENERGY SOURCES IN THE GLOBAL CONTEXT, HIGHLIGHTING THEIR GROWING IMPORTANCE IN A WORLD INCREASINGLY AWARE OF ENVIRONMENTAL ISSUES AND EVOLVING ENERGY NEEDS.
Keywords: Energy plans; Renewable Energy; Energy Matrix; Energy Transition